The Analysis of Interlingual and Intralingual Interference in Children’s Literature Translation Project - Mozes Kurniawan (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
Translation is important in preparing children's literature, especially in children's education. When a prospective teacher does not correctly translate teaching materials, children will be impacted by such inaccuracies such as learning confusion, improperly instilled socio-cultural values and even inadequate intellectual development. The disturbances mentioned are under these two condition such as: interlingual interference (also known as transfer between languages) and intralingual interference (also known as transfer in one language) which is reflected from the translation of English-language teaching materials. This research was a descriptive research aiming to find out, describe and explain the interlingual and intralingual interference found in children’s literature translation project. Participants of this research were students who joined in English Language Learning class of Early Childhood Teacher Education study program, Faculty of Teacher Training and Education, Universitas Kristen Satya Wacana Salatiga. By using translation task/project and semi-structured interview, the research data was collected. The result showed that students still encounter interlingual and intralingual interference especially in some categories. This finding triggered English language practitioners to cope with translation disorder in order to produce the best translated material for children’s education.